The Effect of Celery Juice and Boiled Water on Reducing Uric Acid Levels in The Elderly of Tanjung Alam - Andika, Rindy Arabella Margareta; Hasibuan, Ustifina Hasanah; Fitria, Aida (International Journal of Public Health Excellence (IJPHE), 2023)
Background: Uric acid is the end result of the metabolism of purines in the form of nucleoproteins, which are one component of nucleic acids found in the nuclei of body cells. Celery boiled water containing apiin and apigenin is believed to reduce uric acid levels naturally without causing side effects. This study aims to examine the effect of celery boiled water on reducing uric acid levels in the elderly. Purpose of the study: The purpose of this study was to identify the effect of giving celery boiled water on reducing uric acid levels in the elderly in Tanjung Alam Village. Methods: The study used pre-experiments with One Group Pretest Posttes design. Sampling technique with simple random sampling technique. The number of samples was 66 elderly people. Results: The results of statistical analysis using the Paired T-Test test. The results of the Paired T-test test on 66 elderly people showed a decrease in uric acid levels with a p-value of 0.000 (p <0.05). This shows that there is an effect of celery boiled water on reducing uric acid levels in the elderly. Conclusion: Based on the results of the study, there is an effect of giving celery boiled water on reducing uric acid levels in the elderly. Giving this therapy can be used to reduce uric acid levels in the elderly by doing it regularly with 200 cc every morning.